Manajemen Sindrom Koroner Kronik: Laporan Kasus - Rampengan, Starry H.; Cahyono, Alvin E. (Medical Scope Journal, 2025)
Abstract: Over the last decades, the management of chronic coronary syndromes (CCS) has improved rapidly that contributes in the decreasing of cardiovascular mortality. After myocardial infarction, the patient’s condition can improve with the usage of reperfusion therapy with thrombolysis or primary angioplasty and preventive treatment with aspirin and antiplatelet agents, statin, beta-blockers, and renin-angiotensin antagonists. Moreover, percutaneous coronary intervention (PCI) can improve the survival of patients suffering from acute coronary syndrome (ACS). We reported a 49-year-old man, who complained of chest pain for the last one year, which worsened with activity. One day before hospitalization, the chest pain worsened. The patient was diagnosed with CCS CCS (Chronic Coronary Syndrome Canadian Cardiovascular Society) II-III, GERD, hyponatremia, dyslipidemia, hyperuricemia, and dyspepsia. After further examination, a RF-CL of 20% (moderate) was obtained. A Dobutamine Stress Echocardiography examination was carried out resulting a positive ischemic response, then DCA-PCI was performed. The patient went home without any complaints. The management of this patient from diagnosis to therapy is in accordance with the ESC CCS 2024 guidelines. In conclusion, regarding the importance of acute chest pain management, patients with chest pain should not be underestimated and there are many modalities that can be used to confirm the diagnosis of chronic coronary syndromes. Keywords: chronic coronary syndrome; dobutamin stress echocardiography; percutaneous coronary intervention; risk factor-clinical likelihood   Abstrak: Selama beberapa dekade terakhir, manajemen sindrom koroner kronis telah meningkat pesat yang menyebabkan mortalitas kardiovaskular telah menurun secara stabil. Kondisi pasien setelah infark miokard dapat menjadi lebih optimal dengan adanya terapi reperfusi dengan trombolisis atau angioplasti primer dan terapi pencegahan seperti aspirin dan agen antiplatelet lainnya, statin, beta-blocker, dan antagonis renin-angiotensin. Intervensi koroner perkutan (IKP) dapat meningkatkan kelangsungan hidup pasien yang mengalami sindrom koroner akut (SKA). Kami melaporkan seorang laki-laki berusia 49 tahun, dengan keluhan nyeri dada sejak 1 tahun terakhir, diperberat dengan aktivitas. Sehari sebelum masuk rumah sakit, nyeri dada dirasakan memberat. Pasien didiagnosis dengan sindroma koroner kronik CCS CCS (Chronic Coronary Syndrome Canadian Cardiovascular Society) II-III, GERD, hiponatremia, dislipidemia, hiperurisemia, dan dispepsia. Pada pemeriksaan lanjut, didapatkan RF-CL 20% (moderate), kemudian dilakukan pemeriksaan dobutamin stress echocardiography dan didapatkan hasil iskemik respons positif, sehingga dilanjutkan dengan IKP. Penatalaksanaan pasien ini sejak konfirmasi diagnosis sampai terapi telah sesuai dengan Guidelines ESC CCS 2024. Pasien dipulangkan dengan tidak ada keluhan. Simpulan kasus ini ialah terkait tatalaksana nyeri dada akut, pasien dengan nyeri dada tidak boleh diremehkan, dan telah banyak modalitas yang dapat digunakan untuk mendiagnosis sindroma koroner kronik. Kata kunci: sindrom koroner kronik; dobutamin stress echocardiography; intervensi koroner perkutan; risk factor-clinical likelihood